Breakfast preferences and consumption location among children at a median age of 7 in Shenzhen: Implications for managing overweight and obesity. (1st January 2021) - You, Yingbin; Zhang, Fan; Han, Jing; Liu, Ruiguo; Li, Boya; Ding, Zan; Zhou, Hua; Zhang, Qingying
Abstract: Background: Breakfast is commonly described as the most important meal of the day; however, we have little information regarding its relevance for childhood overweight and obesity in southern mainland China. This study aimed to assess the association between breakfast preferences, consumption location and overweight and obesity for children in Shenzhen. Methods: Among 6126 children (median age 7.2 years) at primary schools, 3504 were finally included after a questionnaire survey and physical examination. Ten commonly consumed foods/beverages for breakfast in southern China were exposure variables, and consumption location, total energy demographic and other dietary characteristics were covariates in logistic regression to determine the effect of breakfast preferences on overweight and obesity, estimating odds ratios (ORs) and 95% confidence intervals (CIs). Results: Probability of overweight/general obesity was inversely associated with children eating plain congee for breakfast (adjusted OR 0.689, 95% CI 0.566–0.838), restricted to boys after stratification. Probability of overweight/general obesity and central obesity was positively associated with usually eating steamed rice roll for breakfast (OR 1.309, 95% CI 1.090–1.571 and OR 1.351, 95% CI 1.064–1.717, respectively), but the effect on overweight/obesity remained statistically significant for only boys after stratification. Eating steamed rice roll for breakfast and eating out for breakfast had an additive interaction on overweight/obesity. Additionally, eating bread for breakfast had a mild favorable effect on overweight/obesity but only for girls. Conclusions: Keeping a healthy weight might benefit children who eat plain congee or bread for breakfast in China. However, frequent consumption of steamed rice roll for breakfast and especially eating out could contribute to overweight and obesity. Thus, we need to promote a healthier breakfast pattern among children in southern China to reduce the odds of obesity.